A 75-Mb/s RGB PAM-4 Visible Light Communication Transceiver System With Pre- and Post-Equalization - Wang, Li; Wang, Xuanzheng; Kang, Jian; Yue, C. Patrick (Journal of lightwave technology, 2021)
Visible light communication (VLC) technology employing light-emitting diodes (LEDs) as light sources has the advantages of using the license-free spectrum, being power and cost-efficient and having high security. However, common LED devices have the limitations of narrow bandwidths, nonlinear optical and frequency responses over different bias current levels, which cause inter-symbol interference and signal distortion, especially under high order modulation schemes with large current swings. In view of this, a compact PAM-4 VLC transceiver system employing a white LED as the light source with pre- and post-equalization is proposed. The white LED consists of a red, a green and a blue LED unit (RGB LED). Controlled by 3-bit thermometer codes, three separate drivers with feed-forward equalizers (FFEs) drive the RGB LED units to produce the PAM-4 optical signal. The driving currents from the three drivers with FFEs can be calibrated using digital and analog tunings to eliminate the differences in optical and frequency responses of the RGB LED units. A cascaded continuous-time linear equalizer (CTLE) is used at the receiver side as post-equalization to compensate for the narrow bandwidth of LED units. Based on experimental results, the proposed RGB PAM-4 VLC system can improve the highest achievable data rate by 1.67 times from 28 to 75 Mb/s using the pre- and post-equalization scheme.